2011
DOI: 10.1128/jb.00170-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Mercury-Methylating Strain Desulfovibrio desulfuricans ND132

Abstract: Desulfovibrio desulfuricans strain ND132 is an anaerobic sulfate-reducing bacterium (SRB) capable of producing methylmercury (MeHg), a potent human neurotoxin. The mechanism of methylation by this and other organisms is unknown. We present the 3.8-Mb genome sequence to provide further insight into microbial mercury methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Another genome of strain ND132, also wrongly classified as a Desulfovibrio desulfuricans, is 3,858,580 bp long, contains 3,533 genes with 3,454 coding for proteins and 64 coding for RNA genes (Brown et al 2011a).…”
Section: Genome Comparisonmentioning
confidence: 99%
“…Another genome of strain ND132, also wrongly classified as a Desulfovibrio desulfuricans, is 3,858,580 bp long, contains 3,533 genes with 3,454 coding for proteins and 64 coding for RNA genes (Brown et al 2011a).…”
Section: Genome Comparisonmentioning
confidence: 99%
“…Представники роду Desulfovibrio беруть участь у процесах біомінералізації та біокорозії металів [31][32][33][34]. Для роботи відібрані бактерії з максимальною корозійною активністю (високоагресивні).…”
Section: матеріали та методи досліджень адгезійних властивостей та міunclassified
“…Detailed assessments and comparisons of mercury methylation rates for several Desulfovibrio species that are incomplete oxidizers, including those investigated in this study, have been reported (6, 8). Genome sequences for several SRBs known or predicted to be mercury methylators have been reported (2, 912). …”
Section: Genome Announcementmentioning
confidence: 99%